Electrochemical detection of dioctyl phthalate using molecularly imprinted polymer modified screen-printed electrodes - El-Sharif, H.F.; Patel, S.; Ndunda, E.N.; Reddy, S.M. (Elsevier, 2022)
We report the investigation of electropolymerised molecularly imprinted polymers (E-MIPs) for the determination of dioctyl phthalate (DOP). Low-cost and eco-friendly commercially available screenprinted electrodes (SPEs) were used. E-MIPs were produced using the cyclic voltammetry (CV) technique based on a water-soluble 4-aminophenol as functional monomer. E-MIPs for DOP showed affinity for the template, with 80% binding efficiency and an imprinting factor of 3. The E-MIPs were able to detect absolute levels of DOP in a time-dependent adsorption manner with the presence of 250 mg DOP (equivalent to 12.8 mM) detected in 5 min with a LOD (at 15 min) of 177.1 mg and LOQ of 536.6 mg making them suitable for the measurement of DOP in freshwater when the sample is pre-concentrated.
Keywords: Molecularly imprinted polymers MIPs; Electrochemical polymerisation; Biosensor; Dioctyl phthalate (DOP; di(2-ethylhexyl) phthalate (DEHP); bis(2-ethylhexyl) phthalate; Environmental monitoring; Disposable electrodes